TaleNeprilysin and Neprilysin inhibition in chronic kidney disease - Judge, PK; Haynes, R (Lippincott, Williams & Wilkins, 2021)
Purpose of review Chronic kidney disease (CKD) is associated with increased risk of progression to end-stage kidney disease and cardiovascular events. There is limited evidence that available treatments have beneficial effects on cardiorenal outcomes in all people with nondiabetic CKD. Neprilysin inhibition (NEPi) is a new therapeutic strategy with potential to improve outcomes for patients with CKD.